Revision of the genus Erythromelana Townsend (Diptera: Tachinidae) and analysis of its phylogeny and diversification - Inclan, Diego J.; Stireman, John Iii O. (Zootaxa, 2013)
The Neotropics harbor an enormous diversity of tachinid flies (Diptera: Tachinidae), yet the fauna remains poorly understood. This is especially true of the tribe Blondeliini, which is particularly diverse in this region and in great need of taxonomic attention. Here, the Neotropical blondeliine genus Erythromelana Townsend is revised. This genus is widely distributed from southern Mexico to northern Argentina, with the Andes being a hotspot of diversity. Known hosts belong to the genus Eois Hübner (Lepidoptera: Geometridae). This revision includes the redescription of three previously described species and the description of 11 new species based on characteristics of adults and immatures. The new species are E. arciforceps sp. nov., E. catarina sp. nov., E. convexiforceps sp. nov., E. cryptica sp. nov., E. curvifrons sp. nov., E. distincta sp. nov., E. ecuadoriana sp. nov., E. eois sp. nov., E. leptoforceps sp. nov., E. napensis sp. nov., and E. woodi sp. nov. A morphological database of 62 characters was constructed to assess morphological variation within and among species and species groups using Principal Components Analysis. Means and medians for these morphological traits were calculated to infer phylogenetic relationships using parsimony. Additionally, a maximum likelihood phylogenetic analysis was performed using COI mtDNA sequences for a subset of eight species. Nominal species E. obscurifrons (Wulp) is treated as a nomen dubium within Erythromelana. Two species previously assigned to Erythromelana appear to represent distinct genera with unclear relationships to this genus and are reinstated as monotypic genera: Myiodoriops marginalis Townsend and Euptilodegeeria obumbrata (Wulp), revived status. Biological and phylogenetic data are used to infer modes of diversification within Erythromelana.